2022
DOI: 10.15586/aei.v50i6.693
|View full text |Cite
|
Sign up to set email alerts
|

A new classification option for NSAID hypersensitivity

Abstract: Background: The European Network for Drug Allergy (ENDA) proposed a consensus document for hypersensitivity reactions to nonsteroidal anti-inflammatory drugs (NSAIDs) in 2011. A subgroup of patients with NSAIDs-exacerbated respiratory disease (NERD) develop urticaria/ angioedema type reactions in response to NSAIDs. The Kalyoncu classification might be a novel option to classify patients with NSAID hypersensitivity (NH). In this study, we compare the ENDA and the Kalyoncu classifications. Methods: This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…A Turkish study reported N-ERD as the most prevalent subgroup (32%) and SNIDR as the least frequent (1.5%), with only two patients (1.0%) not fitting the ENDA criteria. 10 The based on a standardized questionnaire, which may have caused recall bias. The lack of biomarkers based on pathogenic mechanisms, such as urinary Leukotriene E4, serum periostin, and other inflammatory markers, limits our ability to classify these patients and provide new insights into this classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Turkish study reported N-ERD as the most prevalent subgroup (32%) and SNIDR as the least frequent (1.5%), with only two patients (1.0%) not fitting the ENDA criteria. 10 The based on a standardized questionnaire, which may have caused recall bias. The lack of biomarkers based on pathogenic mechanisms, such as urinary Leukotriene E4, serum periostin, and other inflammatory markers, limits our ability to classify these patients and provide new insights into this classification.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Developing a comprehensive classification system has been challenging, with multiple classifications proposed in the literature. [4][5][6][7][8][9][10] This diversity in classifications can lead to confusion when interpreting the literature and comparing studies. The latest European Academy of Allergy and Clinical Immunology (EAACI) classification of NSAID hypersensitivity is widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время достоверно не известно, является ли ПГЛКА с сопутствующей хронической крапивницей (ПЛГКА+К) отдельным подтипом хронической крапивницы, или обострение хронической крапивницы может развиться у любого пациента с этой патологией на фоне приёма НПВП [6]. Отмечено, что ЛГ к НПВП у взрослых пациентов чаще развивается у женщин [7,8], а в детской популяции -у мальчиков [9,10]. Основные причинно-значимые НПВП -ацетилсалициловая кислота, производные пропионовой кислоты и метамизол натрия [11][12][13].…”
Section: A C C E P T E D F O R P U B L I C a T I O Nunclassified